2016
DOI: 10.1039/c5ra22309a
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the interaction between poly(vinyl alcohol) and sandy soil for enhanced water retention performance

Abstract: PVA 1795 and 1797 was effective in improving the growth of plants in sandy soil, may be a good alterative of PAM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…The difference between applied 0.1% and 0.2% concentration of PVA were insignificant, but, it had significant effect with applied 0.0 % and 0.05 % on faba bean seed kg fed -1 ., in second season. These results are in agreement with those obtained by Kukal et al (2007), Chandrika et al (2014), Jiang et al (2016) and Yin et al (2016).…”
Section: Faba Bean Yield Response To Various Available Soil Moisture Depletion and Polyvinyl Alcohol Concentrations Treatmentssupporting
confidence: 94%
See 2 more Smart Citations
“…The difference between applied 0.1% and 0.2% concentration of PVA were insignificant, but, it had significant effect with applied 0.0 % and 0.05 % on faba bean seed kg fed -1 ., in second season. These results are in agreement with those obtained by Kukal et al (2007), Chandrika et al (2014), Jiang et al (2016) and Yin et al (2016).…”
Section: Faba Bean Yield Response To Various Available Soil Moisture Depletion and Polyvinyl Alcohol Concentrations Treatmentssupporting
confidence: 94%
“…Hence, the average increased in ETa compared to zero concentration PVA treatment reached 527.18 and 502.39 mm in first and second season, respectively. These results were in agreement with those obtained by Jiang et al (2016), Yin et al (2016) and Abobatta (2018) who observed that the density of chain cross linking creates an expressive amount of free volume between the polymer network. This in turn, combined to the presence of huge number of hydrophilic groups, has the ability of water absorption and retention for large amounts of water, on the order of 10 to 1000 g/g (1.000-100.000%).…”
Section: Water Relations Of Faba Bean Crop: Faba Bean Actual Evaopotranspiration (Eta) Affected By Different Water Regimes and Poly Vinylsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, manual management and improvement measures were also important for coordinating the ES relationships. These measures include building bench terraces to change the topographical conditions and implementing artificial rainwater collection measures to fully utilize water resources (Wei et al, 2016), improving soil properties to increase organic matter and silt content (with greater emphasis on organic fertilizer) (Ankenbauer and Loheide, 2017;Geng et al, 2017), covering the soil surface (e.g., straw mulching) to decrease water evaporation and control soil erosion (Fernández and Vega, 2016), applying chemical measures such as water-retaining agents (Yin et al, 2016) and transpiration-controlling preparation (Li et al, 2015) to decrease water consumption, and finally, employing environmentally friendly tillage methods, such as reduced/ no-tillage, straw retention, crop rotation, forest-crop intercropping, and mix-sowing of shrubs and grass (Fang et al, 2016).…”
Section: Recommendations For Es Regulation Based On Es Trade-offsmentioning
confidence: 99%
“…The cups were kept at room temperature and weighed every 2 d for 6 d. The cups were dried at 80 °C for 24 h to evaporate the residual moisture and weighed. The DWHC retained in the soil was determined from eq where W 1 is the weight of dry soil (g) and W 2 is the weight of wet soil (g).…”
Section: Experimental Sectionmentioning
confidence: 99%